3, 4‐Dihydroxy‐1, 6‐bis(4‐methoxyphenyl)hexa‐2, 4‐diene‐1, 6‐dione, its 4‐methylphenyl analogue, and a potassium salt of 2‐hydroxy‐4‐(4‐methoxyphenyl)‐4‐oxobut‐2‐enoic acid. (11th October 2013) - Nye, Luke; Turnbull, Mark M.; Wikaira, Jan L.
Abstract : Reaction of 4‐methoxyacetophenone with diethyl oxalate under basic conditions produced 3, 4‐dihydroxy‐1, 6‐bis(4‐methoxyphenyl)hexa‐2, 4‐diene‐1, 6‐dione, C20 H18 O6, (1). The molecules lie across a crystallographic inversion centre and intramolecular hydrogen bonding, similar to acetylacetone, is observed, confirming that the molecule is in the di‐enol‐dione tautomeric form. Additional O—H...O hydrogen bonds link the molecules into chains parallel to the b axis. The structure is compared with that of redetermined 4‐methylphenyl compound 3, 4‐dihydroxy‐1, 6‐bis(4‐methylphenyl)hexa‐2, 4‐diene‐1, 6‐dione, C20 H18 O4, (2), which crystallizes in a similar fashion. The salt, catena ‐poly[[μ2 ‐2‐hydroxy‐4‐(4‐methoxyphenyl)‐4‐oxobut‐2‐enoato‐κ 3 O 1, O 2 : O 4 ][μ2 ‐2‐hydroxy‐4‐(4‐methoxyphenyl)‐4‐oxobut‐2‐enoic acid‐κ 2 O 1 : O 4 ]potassium], [K(C11 H9 O5 )(C11 H10 O5 )] n, (3), was isolated as a by‐product of the synthesis of (1). The two organic species are linked by a strong hydrogen bond between the carboxylic acid and carboxylate groups. They are further stabilized and linked into a double‐chain structure via the seven‐coordinate potassium ion.